Engaging the evil empire : Washington, Moscow, and the beginning of the end of the Cold War - Miles, Simon, 1988- (Cornell University Press, 2020)
"This book is about the beginning of the end of the Cold War between 1980 and 1985. The key shift that allowed the Cold War to end was not one from conflict to cooperation but rather from covert to overt engagement, with both superpowers seeing engagement as a means of furthering their own, primarily competitive, goals"--